STRATEGIES OF FORMING LEARNING MOTIVATION FOR ELEMENTARY SCHOOL STUDENTS - DARAWSHA, Ahlam (Acta et Commentationes, Sciences of Education, 2019)
Motivation lies at the basis of the good functioning of human action components, regardless of the activity carried out or the level of procurement of the person making the effort in its realization. In an educational context, motivation acts as a triggering and supportive factor in learning. In order to prevent the lack of productivity characterized by the inversely proportioned ratio between the results obtained and the effort, the teacher has the responsibility to motivate the student by implementing different motivation strategies. This study provides an analysis of the most effective strategies aimed at motivating elementary school pupils to learn: identifying learning needs and motives, stimulating cognitive impulse, convergence and interest capture, stimulating competition, reducing anxiety etc